2008
DOI: 10.1111/j.1600-065x.2008.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10: new perspectives on an old cytokine

Abstract: Summary Interleukin-10 (IL-10) has long been recognized to have potent and broad-spectrum anti-inflammatory activity, which has been unequivocally established in various models of infection, inflammation, and even in cancer. However, because of the marginal successes of the initial clinical trials using recombinant IL-10, some of the interest in this cytokine as an anti-inflammatory therapeutic has diminished. New work showing IL-10 production from regulatory T cells and even T-helper 1 T cells has reinvigorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
779
2
18

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 920 publications
(819 citation statements)
references
References 98 publications
20
779
2
18
Order By: Relevance
“…Here we show for the first time, using two experimental approaches, that abundant IL-10 is spontaneously produced by Treg cells in tumors subcutaneously IL-10 is a crucial cytokine for immune suppression in tumors. Tumor-associated macrophages constitutively express IL-10 [34], thus maintaining an impaired immune status. We and others [35,36] have reported that IL-10 receptor blockade, when combined with TLR agonists and/or other immunostimulatory agents, rescue the functional paralysis of tumor-infiltrating DCs and macrophages toward an efficient cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Here we show for the first time, using two experimental approaches, that abundant IL-10 is spontaneously produced by Treg cells in tumors subcutaneously IL-10 is a crucial cytokine for immune suppression in tumors. Tumor-associated macrophages constitutively express IL-10 [34], thus maintaining an impaired immune status. We and others [35,36] have reported that IL-10 receptor blockade, when combined with TLR agonists and/or other immunostimulatory agents, rescue the functional paralysis of tumor-infiltrating DCs and macrophages toward an efficient cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to IL-6 that is ubiquitously expressed, IL-10 is mainly produced by macrophages and activated T cells. 17 Indeed, depletion of Kupffer cells (liver macrophages) has been shown to abolish induction of IL-10 expression in the regenerating liver after PHx. 21 Taken together, these findings suggest that after PHx, elevated levels of LPS in the liver stimulate Kupffer cells via targeting TLR4 to produce IL-10 that subsequently inhibits inflammatory response and liver regeneration.…”
Section: Up-regulation Of Il-10 After Phx In a Tlr4-dependent Mannermentioning
confidence: 99%
“…17 IL-10 exerts its function via binding IL-10R1 and IL-10R2, followed by activation of STAT3 in myeloid cells. Conditional deletion of STAT3 in myeloid cells results in enhanced inflammatory response and inflammation in various organs including the liver.…”
Section: Il-10 Plays An Important Role In Tempering Inflammatory Respmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it is still possible that one or more regulatory elements necessary for hIL-10 expression lie outside of the BAC transgene or that one or more of the multitude of transcription factors shown to regulate IL-10 expression in the mouse, including STAT3, STAT4, AP-1, CREB, and cMAf (reviewed in ref. 17), might bind suboptimally to the appropriate sites in the transgene. The latter possibility seems especially relevant in light of recent studies by Saraiva et al (18), demonstrating that IL-10 production by Th1 cells requires high and sustained levels of antigen and IL-12, suggesting that the development of these regulatory cells is tightly controlled.…”
Section: Myeloid But Not T Cells Express Hil-10bacmentioning
confidence: 99%